The Palestine question II : publications (Filmed by the University of Chicago Library Photoduplication Laboratory for the Middle Eastern Microfilm Project at the Center for Research Libraries, 1993)
Collection of 35 documents in Arabic, English and French on the political situation in Palestine, focusing primarily on Arab-Israeli conflicts, published by various organizations in 1936-1990; filmed from originals held by the Library of Congress.